The seven husbands of Evelyn Hugo [compact disc, unabridged] - Reid, Taylor Jenkins (Simon & Schuster Audio, 2017)
Aging and reclusive Hollywood movie icon Evelyn Hugo is finally ready to tell the truth about her glamorous and scandalous life. But when she chooses unknown magazine reporter Monique Grant for the job, no one in the journalism community is more astounded than Monique herself. Summoned to Evelyn's Upper East Side apartment, Monique listens as Evelyn unfurls her story: from making her way to Los Angeles in the 1950s to her decision to leave show business in the late 80s, and, of course, the seven husbands along the way. As Evelyn's life unfolds, Monique begins to feel a very a real connection to the actress. But as Evelyn's story catches up with the present, it becomes clear that her life intersects with Monique's own in tragic and irreversible ways.